Dissolved methane distribution in surface seawater and its controlling factors in mid- and high-latitudes in the Southern Ocean - Thi, Ngoc Oanh Bui; Sohiko Kameyama; Hisayuki, Yoshikawa-Inoue; Masao, Ishii; Daisuke, Sasano; Katsuro, Katsumata; Hiroshi, Uchida (2015)
第6回極域科学シンポジウム 分野横断セッション：[IB1] 海氷域における生物地球化学的研究 11月17日（火） 統計数理研究所 セミナー室1（D305） conference object